Studi Literatur: Corporate Social Responsibility (CSR) Berbasis International Standard Organization (ISO) 26000 Dalam Upaya Meningkatkan Nilai Perusahaan - Syach, Alqibran; Fajrin, Farid (Study of Scientific and Behavioral Management, 2022)
This research is a qualitative descriptive study using the literature study method, with the aim of knowing the results of the implementation of ISO 26000-based Corporate Social Responsibility (CSR) to increase company value. The results showed that the implementation of corporate social responsibility (CSR) based on the International Standard Organization 26000 in an effort to increase the value of the company by referring to the seven core subjects discussed in ISO 26000, namely: (1) Organizational governance; (2) Human rights (human rights); (3) Labor practices; (4) the environment (the environment); (5) Fair operating procedures (fair operating procedures); (6) consumer issues (consumer issues); (7) Community involvement and development, these seven subjects were issued by the International Organization for Standardization (ISO). Keywords: Corporate Social Responsibility, ISO 26000, Company Value